Russian National Identity and History Today: Research on the Presentation of National Identity in Russian Children’s Books on History - Notarp, Ulrike (Intercultural Communication Studies, 2026)
Russian National Identity and History Today: Research on the Presentation of National Identity in Russian Children’s Books on History